PENGALAMAN PEREMPUAN BEKERJA DAN HADIST SEBAGAI LANDASAN: ANALISIS FENOMENOLOGIS - Binti Aghnia Auliyalloh, Nasrulloh (JIPI (Jurnal Ilmiah Pendidikan Islam), 2026)
Abstract This study aims to analyze the lived experiences of Indonesian women workers in interpreting work dignity, professional challenges, and the role of hadith as an ethical framework in the contemporary workplace. The research employs a qualitative approach using a phenomenological method. The participants consist of eight women of productive working age who are actively employed in both the formal and informal sectors in Indonesia. They were selected through purposive sampling based on criteria of having work experience and a willingness to reflect deeply on their experiences. Data were collected through semi-structured interviews and open-ended narrative questionnaires, and then analyzed using Braun and Clarke’s six-phase thematic analysis. The findings identify three main themes. First, women’s work dignity is constructed through recognition of competence, trust, and consistency in organizational practices, rather than solely through material compensation. Second, the challenges faced by working women arise from the intersection of dual role demands, limited structural flexibility, and the quality of the work environment, all of which influence psychological well-being and the meaning of work. Third, the spirit of hadith—particularly the values of trustworthiness (amanah), honesty, and professionalism—is internalized as an ethical orientation for evaluating work practices and professional relationships. This study contributes academically by bridging research on the phenomenology of women’s work and hadith studies, and by offering an interdisciplinary approach that positions hadith as a relevant and applicable framework for work ethics within the context of modern employment in Indonesia. Keywords: Women Workers; Work Ethics; Work Dignity